2008
DOI: 10.1103/physrevd.78.035014
|View full text |Cite
|
Sign up to set email alerts
|

ProbingCP-violation at colliders through interference effects in diboson production and decay

Abstract: We define a CP-asymmetric observable that is sensitive to CP-violating interactions in the gaugeboson sector. We illustrate the utility of this observable by studying how well the LHC can measure the coefficient of a particular dimension-six W W Z operator. We find that sensitivity at the 10 −3 level is possible at the LHC with 100 fb −1 of integrated luminosity, which would greatly exceed the sensitivity achieved at LEP, and would rival or may even better the indirect sensitivities inferred from related opera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Up to this point the analysis that we have performed has not benefitted from the CPodd nature of the TGV interactions. Different studies [108,[114][115][116] have addressed the CP-odd nature of the anomalous TGVs by constructing some CP-odd orT -odd observable. In particular, in Ref.…”
Section: Cp Violation In W W Z: Collider Bounds and Signaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to this point the analysis that we have performed has not benefitted from the CPodd nature of the TGV interactions. Different studies [108,[114][115][116] have addressed the CP-odd nature of the anomalous TGVs by constructing some CP-odd orT -odd observable. In particular, in Ref.…”
Section: Cp Violation In W W Z: Collider Bounds and Signaturesmentioning
confidence: 99%
“…In particular, in Ref. [115] it was shown that ideally in pp → W ± Z an asymmetric observable based on the sign of the cross-product p q · (p Z × p ) could be a direct probe of CP-violation, where here p q is the four-momentum of the incoming quark. At the LHC, however, p q cannot be fully determined and for this reason we build instead as a reconstructable correlated sign variable…”
Section: Cp Violation In W W Z: Collider Bounds and Signaturesmentioning
confidence: 99%
“…Of particular interest (independently of the naturalness issue) are higher dimensional operators violating CP , which could generate the baryon asymmetry in the Universe. In this work, we examine one such operator, 1 namely O Z ≡ W + µ ν W − ν λZ λ µ where W ± µ ν is the usual field strength tensor for W ± andZ µν ≡ µνρσ Z ρσ is the dual field strength tensor for the Z. O Z has been suggested more than once as a suitable target for LHC searches [1,2]. 2 We shall see that, for a variety of reasons, there is almost no hope of being sensitive to allowed values of the coefficient, α Z , of this operator at the LHC, and so experimentalists would be better off directing their efforts elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we examine one such operator, 1 namely O Z ≡ W + µ ν W − ν λZ λ µ where W ± µ ν is the usual field strength tensor for W ± andZ µν ≡ µνρσ Z ρσ is the dual field strength tensor for the Z. O Z has been suggested more than once as a suitable target for LHC searches [1,2]. 2 We shall see that, for a variety of reasons, there is almost no hope of being sensitive to allowed values of the coefficient, α Z , of this operator at the LHC, and so experimentalists would be better off directing their efforts elsewhere. Along the way, we shall have occasion to point out one or two pitfalls in the logic of effective field theory (EFT) that, while no doubt known to many, are liable to trap the unwary.…”
Section: Introductionmentioning
confidence: 99%
“…The couplingλ Z has also been studied in this context in Ref. [15] in W Z production by measuring the observable…”
Section: Introductionmentioning
confidence: 99%